Dampak Teknologi Biogas Dari Kotoran Sapi Terhadap Lingkungan Dan Ekonomi Peternakan - Fachrurizal (Jurnal Ilmu Peternakan Indonesia, 2025)
This study examines the impact of biogas technology derived from cattle manure on both environmental sustainability and the economic performance of livestock farmers. Using a mixed-method approach, the research combines quantitative measurements of greenhouse gas emission reduction and energy cost savings with qualitative insights from farmers’ experiences. The findings reveal that the application of biogas significantly reduces methane emissions by up to 40–50%, improves the sanitation of livestock environments, and lowers the risks of water and air pollution. Economically, farmers benefit from reduced household energy costs by 30–40% per month and gain additional income through the utilization and sale of bio-slurry as organic fertilizer. Furthermore, the adoption of biogas technology fosters community empowerment and strengthens rural energy resilience. However, challenges such as high initial investment costs and limited technical knowledge remain barriers to wider adoption. Overall, biogas technology is proven to be a sustainable solution that supports environmentally friendly livestock management and improves the economic resilience of farming households, provided that policy support and community participation are strengthened.